Paper moon [videorecording (Blu-Ray)] - Bogdanovich, Peter, 1939-2022; Bogdanovich, Peter, 1939-2022; O'Neal, Ryan; O'Neal, Tatum, 1963-; Kahn, Madeline; Brown, Joe David (Criterion collection ;, 2024)
A con artist and his nine-year-old orphan companion sell Bibles to widows in Depression-era Kansas.